"There Are Always Grounds for Seeking a World That Is More Free and More Just": An Interview with Noam Chomsky on Israel, Palestine, and Zionism. Issue 3 (3rd July 2018) - Chomsky, Noam; Wainwright, Joel; Nir, Oded
Abstract : In this dialogue, Joel Wainwright and Oded Nir interview one of the most influential commentators on Israel and Palestine, Noam Chomsky. Their wide-ranging discussion examines key controversies surrounding the issue: Israeli aggression, the paradigms for potential solutions to the conflict, early Zionism, the Boycott, Divestment, Sanctions campaign, and the analogy between Israel/Palestine to apartheid South Africa.